KONSEP KEBAHAGIAAN PERSPEKTIF ABU NASHR AL-FARABI - ‘Aliyah Usman, Nurul; Khudori Soleh, Achmad (Penerbit Lafadz Jaya, 2026)
Happiness (al-sa'ādah) remains a central theme across philosophy, psychology, and social sciences, yet contemporary views often reduce it to material pleasures, overlooking spiritual dimensions emphasized by Abu Nasr al-Farabi. This study aims to analyze al-Farabi's concept of happiness, focusing on the roles of intellect (potential, actual, active) and soul (vegetative, imaginative, rational powers) as pathways to eternal felicity oriented toward God. Employing a qualitative descriptive approach via library research, the population comprised all relevant literature up to 2025, with a purposive sample of 20-25 high-quality sources from Google Scholar. Instruments included primary texts like Tahsil al-Sa'adah and secondary journals; data were analyzed through qualitative content analysis involving thematic coding, reduction, and triangulation. Findings reveal happiness as the ultimate good achieved via four virtues (theoretical, intellectual, moral, practical) and stages: soul purification, material detachment, divine imitation, and societal guidance. In conclusion, al-Farabi's framework offers a holistic model for modern well-being, surpassing hedonism through intellect-soul perfection.